Tiempo y narrativa en los folguedos del buey en Brasil - Viveiros de Castro Cavalcanti, Maria Laura (Revista de Antropología Social, 2008)
The ox revelries are popular rituals, symbolic behaviors that require intense corporeal activity, with use of costumes, music and dance. Folkloric literature has frequently understood them as folk dramas that enact a particular plot. This paper proposes an understanding of the “ox dramas” as a narrative and tries to grasp the multiple dimensions of time that configure and contextualize these narratives. Studies and recollections and the living facts of popular culture influence each other and are analyzed as parts of a unique social process. This new understanding of the ox revelries requires a critical contextualization of previous studies. These are shown to have been strongly influenced by the ideological and conceptual assumptions and world visions of Brazilian Modernism, specially through Mario de Andrade’s writings and ideas in the 1930’s, and the Brazilian Folkloric Movement in the 1950’s. Os folguedos do boi são formas rituais populares, comportamento simbólico por excelência a exigir intensa atividade corporal, com o uso de fantasias, muita música e dança. De modo recorrente, esses folguedos foram compreendidos na literatura folclórica como sendo originariamente a encenação de um auto popular. Este texto propõe a compreensão alternativa do “auto do boi” como experiência narrativa e busca apreender as múltiplas dimensões de temporalidade que a configuram e contextualizam. Estudos e registros de um lado e os fatos vivos da cultura popular de outro sobredeterminam-se e são aqui compreendidos como integrando um mesmo processo social. A compreensão dos folguedos do boi contemporâneos requer assim a contextualização dos estudos existentes a seu respeito que receberam marcada influência dos pressupostos ideológicos e das visões de mundo do Movimento Modernista, em especial através das formulações de Mário de Andrade nos anos 1930, e do Movimento Folclórico Brasileiros nos anos 1950.